PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DALAM BURSA EFEK INDONESIA - Khoirul Abidin; Daniel Ryan Satya Pratama (Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the effect of profitability, firm size, and the independent board of commissioners on sustainability report disclosure in energy sector companies listed on the Indonesia Stock Exchange. Profitability is proxied by return on assets (ROA), firm size is measured using the natural logarithm of total assets, the independent board of commissioners is measured by the proportion of independent commissioners to the total number of commissioners, and sustainability report disclosure is measured using 117 disclosure items based on the Global Reporting Initiative (GRI) 2021 indicators. The population of this study consists of energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Purposive sampling was employed, resulting in a sample of 39 companies with a total of 117 firm-years. The research method used is structural equation modeling (SEM) based on the inner model, utilizing Smart Partial Least Squares (PLS) version 4. The results indicate that profitability and firm size have a significant effect on sustainability report disclosure, while the independent board of commissioners has no effect on sustainability report disclosure.